2004
DOI: 10.1093/ptj/84.6.510
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Promotion in Physical Therapy in California, New York, and Tennessee

Abstract: Background and Purpose. As health care providers, physical therapists are in an ideal position to address health promotion issues with their patients; yet, little is known about actual health promotion practice patterns or the confidence of physical therapists in engaging in such activities. The purposes of this study were: (1) to investigate perceptions of practice patterns in 4 focus areas of Healthy People 2010 (disability and secondary conditions by assessing psychological well-being, nutrition and overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 11 publications
3
39
0
Order By: Relevance
“…Recent research has indeed highlighted the interest of integrating health promotion in rehabilitation interventions and research (55,56,60). As rehabilitation professionals, physiotherapists, who can be consulted directly without medical referral (71), are well suited to integrate health promotion in their field of practice (21,39,76,90,91). Hence, efforts should be made further to link and integrate principles and practices of health promotion in the field of physiotherapy to improve interventions at the individual, community and population levels.…”
Section: Health Promotion Strategies In Physiotherapymentioning
confidence: 99%
“…Recent research has indeed highlighted the interest of integrating health promotion in rehabilitation interventions and research (55,56,60). As rehabilitation professionals, physiotherapists, who can be consulted directly without medical referral (71), are well suited to integrate health promotion in their field of practice (21,39,76,90,91). Hence, efforts should be made further to link and integrate principles and practices of health promotion in the field of physiotherapy to improve interventions at the individual, community and population levels.…”
Section: Health Promotion Strategies In Physiotherapymentioning
confidence: 99%
“…Exercise and physical activity are both key components of physiotherapy practice and important elements in the management of individuals with obesity. [23][24][25][26][27][28][29][30] Physiotherapists manage clients who have secondary conditions resulting from obesity. For example, an analysis based on data from the Canadian Joint Replacement Registry found that among hip-replacement patients (n ¼ 7,538), 73% were classified as overweight or obese at the time of surgery, as were 87% of knee-replacement patients (n ¼ 9,706).…”
mentioning
confidence: 99%
“…The perception of lack of time and resources is consistent with reported barriers to HPWP across different health care practice settings and disciplines. 29,37,[49][50][51][52] However, the perceived lack of patient interest is not consistent with the literature. Black et al 53 found that patients believed that engaging with PTs in personal discussions of physical activity, weight management, and smoking was appropriate.…”
Section: Discussionmentioning
confidence: 65%
“…18,19,[22][23][24][25][26] The PT literature most frequently addresses physical activity as the primary focus of health promotion. 6,[27][28][29][30][31][32][33][34] The roles of OT and PT in diet, weight management, sleep hygiene, stress, and smoking cessation are also supported in the literature. 6,[34][35][36][37][38][39][40] Hand therapists represent a confluence of education, beliefs, and practice.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation